Turkish Military Terms in Arabic Language - Alzhanbayeva, U; Kokeyeva, D (Farabi Journal of Social Sciences, 2016)
This article is devoted to the study of Turkish loan-words entered into the language of Arabs, and particularly the military terms. The words in Arabic that have Turkish origin mainly take in those of everyday life usage. They are names of everyday household goods, place-names instruments, words meaning kindred, etc. Among them a notableplace are occupied by the military terms. It is because of the army's particular position in the social-political structure of the East's feudal society – in XVI-XVIII centuries in Egypt the ruling class consisted of Turkish army commanders and Mamluk military aristocracy